"I want to feel like I used to feel": a qualitative study of causes of low libido in postmenopausal women. Issue 3 (March 2020) - Thomas, Holly N.; Hamm, Megan; Hess, Rachel; Borrero, Sonya; Thurston, Rebecca C.
Abstract: Objective: Low libido is common among women over 60 and negatively impacts well-being and relationship satisfaction. Causes of low libido in this age group are not well understood. We used qualitative methods to explore older women's perceptions of causes of low libido. Methods: We conducted 15 individual interviews and 3 focus groups (total N = 36) among sexually active women 60 and older who screened positive for low libido using a validated instrument. Interviews were audio-recorded, transcribed, and coded using a codebook developed by two investigators. Codes were examined, and themes related to causes of low libido emerged. Results: Women noted a number of different factors that contributed to low libido. The common factors that women discussed included postmenopausal vaginal symptoms, erectile dysfunction in male partners, fatigue and bodily pain, life stressors, and body image concerns. Women often found ways to adapt to these factors. These adaptations required open communication between partners regarding sex, and some women noted these conversations were difficult or not successful. Conclusions: A wide variety of factors contribute to low libido in women over 60, but many of these factors are addressable. Low libido in older women should not be automatically attributed to "normal" aging or to menopause; providers should take an approach to assessment and treatment that addresses biological, interpersonal and social, and psychological factors. N/A: Video Summary : http://links.lww.com/MENO/A499 Abstract : Supplemental Digital Content is available in the text